Using Digital Media to Improve Students Speaking Skills in EFL Learning: A Descriptive Qualitative Study - Nabila Fitriana Cendra; Anggiera Amalia; Juliani Asy-Syahidah (Jurnal Ilmiah Profesi Pendidikan, 2026)
Speaking skills are an essential component of English as a Foreign Language (EFL) learning, as they enable learners to communicate effectively in academic and social contexts. However, traditional classroom settings often provide limited opportunities for students to practice speaking, which can hinder the development of oral proficiency. This study aims to examine the role of digital media in enhancing speaking skills among English as a Foreign Language (EFL) learners, particularly in improving pronunciation accuracy, fluency development, and reducing speaking anxiety. The study employed a qualitative descriptive approach through literature review. Data were collected from empirical studies, journal articles, and relevant academic sources discussing the implementation of digital media in EFL speaking instruction. The data were analyzed descriptively to identify effective digital strategies for improving speaking skills. The findings indicate that digital media plays a significant role in enhancing speaking skills among EFL learners. Video conferencing platforms increased students’ speaking time substantially, automatic speech recognition applications improved pronunciation accuracy, and short-form social media challenges contributed to fluency gains. In addition, blended approaches that combine synchronous and asynchronous digital tools were found to be more effective than single-tool interventions. Asynchronous digital practice also reduced speaking anxiety, which is a major affective barrier in oral communication. Nevertheless, challenges such as limited teacher training and inadequate infrastructure remain obstacles to effective implementation. The study concludes that digital media can effectively improve EFL learners’ speaking proficiency when supported by appropriate tool selection, teacher professional development, and adaptive pedagogical frameworks that consider learners’ characteristics and contextual needs.